Role of 'One Stop Crisis Centre' in Identifying and Assisting Victims of Violence in an Indian Health Care Setup - Prachi Verma; Payal Puri; Dhruv Sharma; Shreya Singh (University Library System, University of Pittsburgh, 2020)
Introduction: Cases of female targeted violence often go uncounted in India. To identify the unreported cases of violence, Sukoon was established in 2014 as a hospital-based 'One Stop Crisis Centre' (OSCC). Sukoon provides counselling, police assistance and legal aid to the victims. The aim of the present study was to recognize the role of Sukoon in preventing violence against women (VAW) in the region. Methods: Secondary data was extracted from 430 victims who approached Sukoon from August 2014 through January 2017. Data was collected on different variables: age, marital status, nature of violence, medium through which victims approached Sukoon and type of assistance provided. Significance of association of studied factors with the type of assault was investigated using χ2 test. Results: Age of study-victims ranged from 4 to 75 years with a median age of 26 years and mean age of 27.61 years with standard deviation of 10.56 years. Major types of VAW (96.51%) were domestic violence, sexual assault, physical assault and poisoning. The types of violences were significantly associated with victims' age (χ2 =5.76, d.f.=1, p<0.05) and marital status (χ2 = 98.23, d.f=4, p<0.001). About 78% of victims were identified from Sukoon through screening and counseling. Around 69% of the cases were resolved directly by Sukoon or through police assistance. Conclusion: The above results indicate a significant role of Sukoon in screening victims of violence and providing them required assistance within the hospital environment in one location. Such centers should be further promoted by the government to address the issues of VAW.